Consequences of Ethical Behavior and Trust in the Sport Brand Industry in Indonesia - Kurniawati, Kurniawati; Galingging, Debora (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2024)
The sports industry is currently growing rapidly and becoming one of the major markets in the economy. Dynamic competition drives companies to innovate, especially in technology, to increase economic gains. This phenomenon has triggered the emergence of various sports brands, which requires companies to be creative in marketing and building consumer loyalty. This study focuses on the influence of ethical behavior, brand experience, trust, brand authenticity, and brand equity on customer satisfaction of sneaker users Adidas, Nike, Converse, Puma, and Vans in Indonesia. This study uses a hypothesis testing design with cross-sectional data. Data were collected through online questionnaires to 231 respondents selected using purposive sampling. Data analysis was conducted using SEM (Structural Equation Modeling). This research examines ethical behavior, trust, brand experience, brand authenticity, brand equity, and customer satisfaction. The indicators to measure the variables were adapted from previous research and used a Likert scale. The purpose of this study is to analyze the influence of ethical behavior, brand experience, trust, brand authenticity, and brand equity on customer satisfaction of sneaker users. To provide contributions to sneaker brand marketers in understanding the factors that influence customer satisfaction so that they can develop more effective marketing strategies.